Unveiling Significance and Knowledge Construction in Thai Fragrances: Perspectives of Vocational College Instructors in Bangkok - Amparot, Hattapon (Journal of Cultural Approach, 2024)
This qualitative research delved into the meanings and the process of knowledge construction surrounding Thai fragrances as perceived by vocational college instructors in Bangkok. The study employed in-depth interviews guided by experienced instructors from the home economics departments in vocational colleges, including Thonburi Vocational College, Saowapha Vocational College, and Iam Laor Vocational College, with a total of 9 participants. The research utilized semi-structured and in-depth interviews, observation, recordings, and audio recorders. The findings revealed that the meaning of Thai fragrances encompasses four crucial dimensions: 1) fragrance derived from flowers, herbs, and Thai wisdom; 2) cosmetics associated with upper-class society; 3) usage in significant ceremonies; and 4) embodiment of Thai aesthetics. The process of knowledge constriction regarding Thai fragrances is delineated into four steps: 1) knowledge acquisition; 2) attitude formation; 3) behavioral integration; and 4) policy influence, leading to societal changes.